Harmonics mitigation and non‐ideal voltage compensation utilising active power filter based on predictive current control. Issue 13 (1st October 2020) - Alhasheem, Mohammed; Mattavelli, Paolo; Davari, Pooya
Abstract : It is well‐known that the presence of non‐linear loads in the distribution system can impair the power quality. The problem becomes worse in microgrids and power electronic‐based power systems as the increasing penetration of single‐phase distributed generation may result in a more unbalanced grid voltage. Shunt active power filters (SAPFs) are used for improving the power quality and compensating for the unbalance grid voltage. This study presents a modification of the classical control structure based on the finite control set model predictive control (FCS‐MPC). The proposed control structure can retain all the advantages of FCS‐MPC, while improving the input current quality. Furthermore, a computationally efficient cost function based on only a single objective is introduced, and its effect on reducing the current ripple is demonstrated. The presented solution provides a fast response to the transients as well as compensates for the unbalanced grid voltage conditions. A straightforward single loop controller is compared to the conventional way of realising the active power filters, which is based on space vector pulse width modulation. The simulation results have been obtained from MATLAB/SIMULINK environment, while the obtained experimental results, utilising a 15 kVA power converter, highlight the effective performance of the proposed control scheme and verifies the introduced MPC‐based method as a viable control solution for SAPFs.